Cyclooxygenase-2 inhibition improves amyloid-beta-mediated suppression of memory and synaptic plasticity - ROWAN, MICHAEL JOSEPH; ANWYL, ROGER; WANG, QIN-WEN (Oxford University Press, 2008)
Non-steroidal anti-inflammatory agents (NSAIDs) are associated with a marked reduction in the risk of developing Alzheimer's disease, a form of dementia characterized by the accumulation of amyloid plaques containing the amyloid-? protein (A?). Studies of the effects of NSAIDs upon the inflammatory response surrounding amyloid plaques and upon the generation of A? from the amyloid precursor protein (APP) have led to two proposed mechanisms by which NSAIDs may protect against Alzheimer's disease: one, the selective lowering of A?42 by a subset of NSAIDs; and two, the reduction of inflammation. Although Alzheimer's disease is a disorder of brain and synaptic function, the effects of NSAIDs on A?-mediated suppression of synaptic plasticity and memory function have never been reported. We therefore investigated how three different NSAIDs, chosen for their distinct effects on A?42 production and the inhibition of the cyclooxygenase (COX) isoenzymes, COX-1 and COX-2, affect memory function and synaptic plasticity. By focusing upon brain and synapse function, we made novel observations about the effects of NSAIDs on A?-mediated neural processes. Here we report that the selective inhibition of COX-2, but not COX-1, acutely prevented the suppression of hippocampal long-term plasticity (LTP) by A?. The non-selective NSAIDs, ibuprofen and naproxen, and a selective COX-2 inhibitor, MF-tricyclic, each restored memory function in Tg2576 mice over-expressing APP, and also blocked A?-mediated inhibition of LTP. There was no advantage of ibuprofen, a selective A?42-lowering agent (SALA), over the non-SALAs, naproxen and MF-tricyclic. The beneficial effects on memory did not depend upon lowered levels of A?42 or the inflammatory cytokines, tumour necrosis factor (TNF-) and interleukin 1? (IL-1?). Intriguingly, improved memory function was inversely related to prostaglandin E2 (PGE2) levels. Conversely, exogenous PGE2 prevented the restorative effects of COX-2 inhibitors on LTP. The data indicate that the inhibition of COX-2 blocks A?-mediated suppression of LTP and memory function, and that this block occurs independently of reductions in A?42 or decreases in inflammation. The results lead us to propose a third possible mechanism by which NSAIDs may protect against Alzheimer's disease, involving the blockade of a COX-2-mediated PGE2 response at synapses.
PUBLISHED
Keywords: Neuroscience; synaptic transmission; Alzheimer's disease; Non-steroidal anti-inflammatory agents